The Effect of Multinational Status and Industry Cyclicality on Corporate Leverage: A Study of Consumer Companies on the Indonesian Stock Exchange - David Tampi; Lukman Hanif Arbi (Eduvest - Journal of Universal Studies, 2026)
This research aims to analyze the effect of multinational status and industry cyclicality on the leverage of consumer companies listed on the Indonesia Stock Exchange. Multinational status is proxied by Foreign Sales to Total Sales (FSTS) and Foreign Assets to Total Assets (FATA), while leverage is measured using LEV and LOGDER. This study used quarterly panel data of consumer cyclical and consumer non-cyclical companies during the 2020–2024 period. The analysis method used is two-way fixed effect panel regression with firm fixed effects, time fixed effects, and clustered standard errors at the firm level. The results show that FATA has a positive and significant effect on leverage, while FSTS does not have a significant effect. This indicates that multinationalism reflected through foreign assets is more relevant in explaining corporate financing decisions than foreign sales. In addition, ROA and current ratio have a negative effect on leverage, while growth asset has a positive effect on leverage. Additional analysis shows that FSTS lagged from one to four quarters does not have a significant effect, and the effect of FATA is more evident among consumer non-cyclical companies. This study concludes that leverage decisions among consumer companies in Indonesia are influenced by international involvement, profitability, liquidity, and asset growth.